Pertanggungjawaban Pidana Korporasi dan Pengurusnya dalam Penegakan Kerusakan Lingkungan Hidup akibat Limbah B3 - Carwan; Sari Indah Lestari (Syntax Idea)
Environmental damage often involves corporations as industrial actors, and legislation in Indonesia has recognized corporations as legal subjects that can be held criminally responsible. This research aims to explore and analyze the concept of corporate criminal liability in the context of environmental damage caused by B3 waste in Indonesia. The main focus of the research is on the legal provisions governing environmental crimes, with special emphasis on Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH), Law Number 41 of 1999 concerning Forestry (UU Forestry), and Law -Law Number 39 of 2014 concerning Plantations (Plantation Law). This research examines Gillies' view which states that corporations can be considered "persons" in the eyes of the law, which allows the imposition of criminal liability on corporations as legal entities. However, the concept of corporate criminal liability, especially through the doctrine of "Vicarious/Derivative Individual Liability," raises questions about justice and ethics in criminal law enforcement. This research uses legal document and literature analysis methods to evaluate the relevance, effectiveness and fairness of the concept of corporate criminal liability in the context of environmental damage caused by B3 waste. The research results show that in a theoretical context, criminal liability of corporations and corporate administrators has a different conceptual basis. However, in practice, the construction of vicarious or derivative individual responsibility often causes law enforcers to attribute corporate criminal liability to corporate administrators without considering personal fault. This creates ambiguity between the criminal liability of corporations and corporate administrators, considering that both have different conceptual bases.